eATP sensing by the purinergic receptor PA2072 for allosteric modulation in intracellular c-di-GMP signaling - Yan Zhang; Xiaojing Gao; Yunjie Xiao; Yajing Duan; Wangxin Xiao; Yangyang Xu; Tingting Yang; Huimin Zhang; Cheng Chen; Shuo Shi; Xun-Cheng Su; Xinghua Jin; et al. (Proceedings of the National Academy of Sciences, 2025)
Extracellular ATP (eATP) has emerged as a crucial signaling molecule across eukaryotic and prokaryotic domains, modulating diverse cellular functions by activating purinergic receptors to initiate intracellular signaling cascades. However, the structural and molecular mechanisms underlying eATP sensing and signaling by prokaryotic receptors remain largely unknown. Here, we demonstrate that the receptor PA2072 in Pseudomonas aeruginosa is responsible for recognizing eATP to down-regulate intracellular cyclic di-GMP levels. The periplasmic CHASE4 domain of PA2072 specifically binds and hydrolyzes eATP, exhibiting ATPase activity both in the presence and absence of a divalent cation cofactor. Structural elucidation of the PA2072 CHASE4 domain in its monomeric and complex states unveils an exquisite molecular switch governed by the oligomeric state. ATP hydrolysis by the catalytically active monomeric form is coupled to homodimerization, concomitantly deactivating its ATPase activity and initiating intracellular phosphodiesterase activity. These findings open avenues for understanding interkingdom eATP signaling and developing targeted therapeutic interventions.